A rural revitalization model based on regional livelihood capital: A case study of Diqing, China - Zhu, Siji; Sun, Jun; Wu, Yingmei; Yu, Bohao; Li, Hong; Xia, Tianshun; Zhang, Xiaomei; Liang, Xuqi; Zhu, Guifang (Frontiers in Environmental Science, 2023)
Improving livelihood capital is beneficial for implementing China’s Rural Revitalization Strategy (RRS); however, researchers have not focused on the regional attributes of livelihood capital. Thus, this study proposes the new concept of regional livelihood capital to guide RRS implementation. A comprehensive measurement method and official government statistics were used to analyze regional livelihood capital characteristics in Diqing. The results demonstrate that, from 1993 to 2020, Diqing’s regional livelihood capital index increased steadily from 0.058 to 0.356, and its structure continued to diversify; however, its level remains low. The natural capital index fluctuated between 2.044 and 2.284, and always had absolute advantages. The financial capital index increased rapidly from 0.024 to 1.396 and is the core driving force for the growth of regional livelihood capital. The physical capital index increased steadily from 0.056 to 0.456. The growth of social and human capital index was slow and weak, with an average annual growth rate of only 4.42% and 1.07%, respectively, which represents a weakness in regional livelihood capital. Based on regional livelihood capital characteristics and Diqing’s economic circumstances, a targeted rural revitalization model was developed according to the dynamics of the organic system of regional livelihood capital, in which natural capital is considered the foundation, financial capital the power, physical capital the medium, and social and human capital the ultimate goals. The main direction of energy is “natural capital → financial capital → physical, social, and human capital.” Simultaneously, the reverse energy feedback should also be emphasized to promote the sustainable operation of this system. This study provides a new theoretical perspective of regional livelihood capital for the implementation of RRS, as well as guidance for the practice of RRS in Diqing and other similar areas.